2005
DOI: 10.1103/physrevlett.94.047401
|View full text |Cite
|
Sign up to set email alerts
|

Single-Beam and Enhanced Two-Beam Second-Harmonic Generation from Silicon Nanocrystals by Use of Spatially Inhomogeneous Femtosecond Pulses

Abstract: Optical second-harmonic generation (SHG) is used as a noninvasive probe of the interfaces of Si nanocrystals (NCs) embedded uniformly in an SiO2 matrix. Measurements of the generated SH mode verify that the second-harmonic polarization has a nonlocal dipole form proportional to (E x Delta inverted) E that depends on inhomogeneities in the incident field E, as proposed in recent models based on a locally noncentrosymmetric dipolar response averaged over the spherical NC interfaces. A two-beam SHG geometry is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 17 publications
1
53
0
Order By: Relevance
“…The FHG work, done with the objective of interpreting data obtained by the Downer group on surfaces of varying roughness [28], showed that interface angles were not always those of the bulk, a result also found by Kwon et al [5] Our most recent application, to amorphous (a-) SiO 2 [14], was intended as a first step toward understanding the data of Figliozzi et al [29] on crystalline Si nanoparticles embedded in SiO 2 . Among other results, this work showed that the Liénard-Wiechert expression for radiation from an accelerated charge, although valid for linear optics, did not incorporate the relativistic contribution and hence could not be used for NLO.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The FHG work, done with the objective of interpreting data obtained by the Downer group on surfaces of varying roughness [28], showed that interface angles were not always those of the bulk, a result also found by Kwon et al [5] Our most recent application, to amorphous (a-) SiO 2 [14], was intended as a first step toward understanding the data of Figliozzi et al [29] on crystalline Si nanoparticles embedded in SiO 2 . Among other results, this work showed that the Liénard-Wiechert expression for radiation from an accelerated charge, although valid for linear optics, did not incorporate the relativistic contribution and hence could not be used for NLO.…”
mentioning
confidence: 85%
“…This lateral gradient can determine among other phenomena the spatial pattern of the emerging radiation, for example, the 2-lobed pattern reported in Ref. [29] for SHG from amorphous material under Gaussian-beam excitation [14]. Since lateral gradients can be engineered, for example through the use of crossedbeam excitation, this may be of considerable importance in the future.…”
mentioning
confidence: 97%
“…Dispersion of both the ordinary and extraordinary refractive indices of ZnO are taken from reference (Figliozzi et al, 2005).…”
Section: Evaluation Of the Optical Axis Tilt Of Zinc Oxide Filmsmentioning
confidence: 99%
“…Dipolar SHG is allowed through a surface contribution arising at the interface between centrosymmetric materials where centrosymmetry is broken [1,2]. However, when higher-order multipole interactions [3,4], such as magnetic-dipole and electric-quadrupole interactions, are taken into account, SHG can occur even inside bulk centrosymmetric materials, which was observed in several experiments [5][6][7][8]. When SHG is used as a surface or interface probe, it is essential to separate bulk contributions from the measured SH signal and verify that such multipolar contributions are actually negligible [9].…”
mentioning
confidence: 99%